Maternal obesity is associated with increased maternal and offspring morbidity in both primiparous and multiparous women. (18th April 2012) - Denison, FC; Scotland, G; Bhattacharya, S; Mahmood, T; Morris, C; Norman, JE; Raja, A; Lee, AJ
Abstract : Aim: To determine the effect of maternal body mass index (BMI) on obstetric and perinatal outcomes in all pregnancies at a population level in Scotland. Methods: All women with singleton pregnancies who delivered in Scottish maternity units from 01/01/2003 until 31/12/2009 were included (124, 280 deliveries from 109, 592 women). Women were grouped by WHO BMI criteria with BMI 18.5<25kg/m2 used as the reference group. Data were analysed by univariate tests and random effects hierarchical regression. A fixed effects model was used for sensitivity analyses. Odds ratios (OR) were adjusted for maternal age, deprivation and smoking. Results: Overweight, obese and morbidly obese women respectively were at an increased risk of essential hypertension (adjusted OR 1.87, 95% confidence interval (CI)1.18-2.97, 11.90 (7.18-19.72) and 36.10 (18.33-71.10)), pregnancy induced hypertension (1.76 (1.6-1.95), 2.98 (2.65-3.36) and 4.48 (3.57-5.63)), pre-existing diabetes (2.54 (1.79-3.61), 3.76 (2.59-5.47), 7.71 (4.04-14.71)), gestational diabetes (3.39 (2.30-4.99), 11.90 (7.54-18.79), 67.40 (37.84-120.03)), induction of labour (IOL) (1.30 (1.25-1.35), 1.64 (1.57-1.72), 1.97 (1.78-2.18)), elective caesarean section (CS) (2.06 (1.84-2.30), 4.61 (4.06-5.24) 17.92 (13.20-24.34) or emergency CS (1.94 (1.71-2.21), 3.40 (2.91-3.96) 14.34 (9.38-21.94) and iatrogenic preterm birth (1.25 (1.10-1.42), 1.45 (1.26-1.68) 2.12 (1.57-2.86)) compared to women with normal BMI. Sensitivity analyses demonstrated for women with normal BMI in earlier pregnancies, becoming obese and morbidly obese in subsequent pregnancies was associated with increased risk of IOL, CS and neonatal unit admission >48 hours, respectively (all p<0.05). Conclusion: Maternal obesity has adverse outcomes for obstetric and perinatal health for all pregnant women, regardless of parity.